2007
DOI: 10.1086/515399
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load in Blood Is Correlated with Disease Severity of Neonatal Coxsackievirus B3 Infection: Early Diagnosis and Predicting Disease Severity Is Possible in Severe Neonatal Enterovirus Infection

Abstract: We conducted a study during an outbreak of coxsackievirus B3 infection in 2005 and found that viral RNA could be detected in patients' blood specimens soon after the onset of fever, and the level of viral RNA was positively correlated with disease severity. Timely diagnosis is possible in severe neonatal enterovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…This persistence during chronic cardiac disease suggests that antiviral drugs might be useful in the clinic. Furthermore, regarding acute infections in neonates and infants, it was shown that the initial viral load correlates with disease severity (71). Thus, a therapeutic window exists that may also allow an effective treatment of acute illness by antiviral molecules.…”
Section: Vol 82 2008 Crystal Structure Of Coxsackievirus Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…This persistence during chronic cardiac disease suggests that antiviral drugs might be useful in the clinic. Furthermore, regarding acute infections in neonates and infants, it was shown that the initial viral load correlates with disease severity (71). Thus, a therapeutic window exists that may also allow an effective treatment of acute illness by antiviral molecules.…”
Section: Vol 82 2008 Crystal Structure Of Coxsackievirus Polymerasementioning
confidence: 99%
“…Infections caused by coxsackievirus B serotype 3 (CVB3) are at the origin of 20 to 30% of all human cases of acute and chronic myocarditis (19). Furthermore, CVB3 causes acute infections in neonates and infants leading to febrile illness and meningitis, as well as hepatitis and coagulopathy in severe cases (71). To date, no vaccine or specific anticoxsackievirus drug is approved (2,60).…”
mentioning
confidence: 99%
“…During EV-A71 infection, viraemia early after the onset of disease was related to severe CNS involvement in young children (Cheng et al, 2014) and to neurological impairment in experimentally infected rhesus monkeys (Zhang et al, 2011). In neonates infected with coxsackievirus B3 (CV-B3; EV-B), a high blood viral load was related to greater disease severity (Yen et al, 2007). Using sensitive quantitative gene amplification techniques to amplify viral RNA from the cerebrospinal fluid (CSF), it was possible to detect evidence of EV infection of the CNS in patients with aseptic meningitis early after the onset of disease in both children and adults (Volle et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…IVIG therapy is potentially beneficial for neonates with severe enteroviral diseases. Patients may experience a more rapid clearance of viremia and viuria after IVIG therapy, which contains pathogen-specific neutralizing antibodies [8,15,24]. In addition, IVIG is protective for acute viral myocarditis in animal models and in a clinical trial [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients had EV identified from multiple sites and included throat swab in 56 patients, rectal swab in 53, CSF in 36, urine in 26, blood in 5, and ascites in 1. Five cases in 2005 also had CB3 detected in the blood by real-time polymerase chain reaction [15]. No significant association was observed between the serotype of enteroviruses and prognosis.…”
Section: Epidemiological and Clinical Informationmentioning
confidence: 93%